Structural basis for the assembly and modulation of human M-channels - Lu, Fangzhou; Huang, Xiaoshuang; Cai, Guanxing; Xie, Yuzhen; Fan, Xiao; Huang, Jian (浪淘沙预印本平台, 2025)
Human M-channels, primarily assembled by heteromeric KCNQ2/KCNQ3 subunits, are critical regulators of neuronal excitability, and loss-of-function mutations in either subunit are linked to epileptic disorders. Yet, the molecular mechanisms underlying heteromeric assembly, gating, and pharmacological modulation have remained largely elusive. Here, we present high-resolution cryo-EM structures of human M-channels in apo and activator-bound states, revealing a dominant asymmetric 3:1 and a minor staggered 2:2 stoichiometry of KCNQ2 to KCNQ3, with consistent ratios across datasets. We further examine the mechanisms of action (MOAs) of two distinct modulators: ICA-110381 selectively engages and stabilizes activated KCNQ2 voltage sensors, whereas XEN1101 occupies pore fenestrations and promotes channel opening through a PIP2-assisted cooperative gating process. Electrophysiological analyses corroborate these observations, establishing the basis for subtype-selective modulation, cooperative gating, and KCNQ3-driven low-voltage activation. Together, our findings provide a foundation for interpreting pathogenic mutations and advancing the rational design of next-generation antiepileptic therapeutics targeting the M-channels.